Description Of The Age Of Patient With Covid-19 Cases At RSUD I Lagaligo - Stevia Vania Finriani (-, 2022)
Coronavirus Disease 2019 (COVID-19) is an infectious disease caused by Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2). SARS-CoV-2 is a new type of coronavirus that has never been previously identified in humans. The addition of the number of Covid-19 cases took place quite quickly and there had been spread between countries so that Covid-19 was declared a pandemic by WHO on March 11, 2020. The number of cases globally was 209,201,939 cases with 4,390,467 deaths worldwide (CFR 2, 1%). In Indonesia there were 3,930,300 cases with 122,633 deaths (CFR, 3.1%) and in South Sulawesi there were 988,889 cases with 1,807 deaths. Older people are at risk for Covid-19 because they tend to have long-term health problems, the immune system tends to weaken making it harder for older people to fight infection, lung tissue becomes less elastic over time, and inflammation in older people can be more intense. , causing organ damage. The purpose of this study was to determine the age description of patients with COVID-19 cases at RSUD I Lagaligo. This research is an analytical study with a case control design. The data in this study used secondary data from epidemiological investigation data and medical record data for the period January 1 to August 31, 2021 who were hospitalized in the Covid-19 isolation room at RSUD I Lagaligo with a total sample of 1,296 respondents. Data analysis used univariate and bivariate analysis. The results showed that there was a statistically significant relationship between age and Covid-19 cases with a p-value of 0.01 and an OR value of 1.45, which means that people aged 65 years have a 1.47 times greater risk of being confirmed. positive compared to patients aged 65 years. The conclusion is that all ages are at risk of being confirmed positive for Covid-19, and productive ages are most at risk of Covid-19 due to high mobility and social activities. This can be prevented by continuing to carry out health protocols. Keywords : Covid-19, Pandemic, Age